2005
DOI: 10.1073/pnas.0508643102
|View full text |Cite
|
Sign up to set email alerts
|

T cell Ig and mucin 1 (TIM-1) is expressed on in vivo -activated T cells and provides a costimulatory signal for T cell activation

Abstract: Polymorphisms in TIM-1, a member of the T cell Ig and mucin (TIM) domain family, are associated with relative susceptibility to the development of T helper 2-dominated immune responses such as in allergic asthma. Recent data have also suggested that ligation of TIM-1 can augment T cell activation. We have found that the TIM-1 protein is expressed on CD4 ؉ T cells in vivo after intranasal immunization. Ectopic expression of TIM-1 during T cell differentiation results in a significant increase in the number of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
156
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(169 citation statements)
references
References 32 publications
13
156
0
Order By: Relevance
“…6). These results are in agreement with a recent study in which reporter constructs were used to study promoter engagement after murine TIM-1 overexpression (18). In this study, it was shown that TIM-1 expression induced transcription from the IL-4 and NFAT/AP-1 promoters, signals which would be expected to be induced upon TCR activation.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…6). These results are in agreement with a recent study in which reporter constructs were used to study promoter engagement after murine TIM-1 overexpression (18). In this study, it was shown that TIM-1 expression induced transcription from the IL-4 and NFAT/AP-1 promoters, signals which would be expected to be induced upon TCR activation.…”
Section: Discussionsupporting
confidence: 92%
“…The activity of ITK is therefore consistent with the hypothesis that TIM-1 is a driver of Th2 T cell differentiation. In contrast, we and others have noted that in mouse systems TIM-1 enhances T cell proliferation and Th2 effector function (i.e., cytokine production) without necessarily dampening Th1 activity (15,18). Thus, whether phosphorylation of ITK is sufficient to drive Th2 differentiation during TIM-1-induced T cell activation remains uncertain.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…TIM‐1 is a member of the TIM family of cell surface phosphatidylserine receptors in humans and in mice12 that directly couples to phosphotyrosine‐dependent intracellular signaling pathways13 and provides a costimulatory signal for T cell activation 13. TIM‐1 has recently been found to be predominantly expressed on regulatory B cells 14.…”
Section: Introductionmentioning
confidence: 99%